Consumer Attitude towards FMCGs: A Comparative Study of Private Labels and National Brands - Neelmani, Nilesh (Indian Journal of Marketing, 2011)
The Indian retail scene is all poised for a tremendous growth and is estimated to reach 54 billion by the year 2012, with an annual growth rate of about 9 percent. With the approval of 51% direct investment by Government of India in single brand retail showrooms, foreign retail majors like Tesco, Walmart and Carrefour are all set in to enter the Indian market. All these companies are known for their Private Labels. Private Label is an area in marketing, which has experienced a high degree of growth in the last decade. The objective of the present study was to compare consumer attitude towards Private Labels and National Brands. For the purpose of measuring the consumer attitude, ’Adequacy Importance’ model (Cohen, Fishbein and Ahtola, 1972) was used. As per the requirement of the present study, survey was conducted in different store locations of Food Bazaar in Hyderabad with the help of a structured questionnaire based on attributes like quality, price, freshness, packaging etc. Pilot study was conducted (for n=48) to check the reliability of the instrument. Total 200 responses were collected by using random sampling method. Mean and standard deviations were computed, and t-test for comparing equality of means was applied. The study concludes that price continues to be one of the most important factors for the growth of Private Labels. Consumers’ attitude towards Private Labels has come closer to that of National Brands on some other attributes also.